PEMBUATAN LKS DENGAN PENDEKATAN SAINTIFIK TERINTEGRASI NILAI KARAKTER PADA MATERI KERJA DAN MOMENTUM UNTUK SISWA KELAS X SMA - Rima Melani Putri; Yenni Darvina; Syafriani Syafriani (PILLAR OF PHYSICS EDUCATION, 2017)
Scientific approach and integration of caracter value was important in physics learning. Both of them can improve the holistic competencies students including attitude, knowledge, and skills. In reality, used of scientific approach in physic learning was low with average value was 60%. Applying of caracter value in learning process was less with average value was 57%. One of the solution was to design a student worksheet of scientific approach and integrared caracter value  to student of ten class.The purpose of this study were to produce student worksheet with saintific approach and to determine the validity of student worksheet. This Research and Development (R&D). The step wasknowing the potency and problem,data collection,design, validation, and revision product.  Instrument were used in this research validation sheet.Data analysisconsist of descriptive statistic graph method. The were two main research result. First, product was student worksheet. Second, student worksheet was very valid with average value was 85,96